PERAN TEKNOLOGI DALAM PEMBELAJARAN PENJASORKES PADA KELAS 4 SD NEERI NO. 101470 SOBAR - Pasaribu, Yusti Andayati; Harahap, Rita Nur’Ain; Yusril, Rizky; Asfiati, Asfiati (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This research aims to analyze the role of technology, especially infocus media, in learning Physical Education, Sports and Health (Penjasorkes) for class IV students at SDN No. 101470 Buddy. The research method used was Classroom Action Research (PTK) which involved 15 students. The research results show that the use of infocus media can improve student learning outcomes. Before using infocus media, only 33.33% of students achieved the Minimum Completeness Criteria (KKM). After the intervention, the completion percentage increased to 80%. These findings show that using infocus as a learning medium can increase student participation, concentration, and better understanding of the material.